Encyclopedia of Megafauna and Dinosaurs - Wadsworth, Mabel, author 648685; Mowery, Juliet, author 648272 (Delhi, India : Academic Studio, 2012)
This is a well written Encyclopedia of Megafauna and Dinosaurs.